PDX1 is the cornerstone of pancreatic β-cell functions and identity - Ebrahim, Nour; Shakirova, Ksenia; Dashinimaev, Erdem (Frontiers in Molecular Biosciences, 2022)
Diabetes has been a worldwide healthcare problem for many years. Current methods of treating diabetes are still largely directed at symptoms, aiming to control the manifestations of the pathology. This creates an overall need to find alternative measures that can impact on the causes of the disease, reverse diabetes, or make it more manageable. Understanding the role of key players in the pathogenesis of diabetes and the related β-cell functions is of great importance in combating diabetes. PDX1 is a master regulator in pancreas organogenesis, the maturation and identity preservation of β-cells, and of their role in normal insulin function. Mutations in the PDX1 gene are correlated with many pancreatic dysfunctions, including pancreatic agenesis (homozygous mutation) and MODY4 (heterozygous mutation), while in other types of diabetes, PDX1 expression is reduced. Therefore, alternative approaches to treat diabetes largely depend on knowledge of PDX1 regulation, its interaction with other transcription factors, and its role in obtaining β-cells through differentiation and transdifferentiation protocols. In this article, we review the basic functions of PDX1 and its regulation by genetic and epigenetic factors. Lastly, we summarize different variations of the differentiation protocols used to obtain β-cells from alternative cell sources, using PDX1 alone or in combination with various transcription factors and modified culture conditions. This review shows the unique position of PDX1 as a potential target in the genetic and cellular treatment of diabetes.